Desempenho e características de carcaça de novilhos Jersey terminados com níveis de suplementação em pastagem de inverno - Rieger, Renan Diego (2023)
This study aimed to evaluate the animal performance and carcass characteristics of young Jersey steers fed with levels of supplementation on black oat and ryegrass pasture. The experimental design was completely randomized with three treatments and three area replications. Treatments consisted of supplementation levels of 0.8; 1.1 and 1.4% of body weight. The experimental of 2.25 ha was used, consisting of a black oat + ryegrass pasture established by overseeding in the Aruana grass pasture. Twenty-six Jersey steers with 13.9 months of age and 236.9 kg of initial body weight were used. A continuous stocking system with variable load was used, using two test animals per paddock and a variable number of regulator animals, maintaining the forage canopy at an average height of 19.01 cm. The animals were weighed at the beginning and end of the experiment after fasting for 14 hours. The animals were slaughtered in a commercial slaughterhouse after fasting solids and liquids for 14 hours. Average daily gain, body weight and age at slaughter, hot and cold carcass weight, hot and cold carcass yield, cooling loss, fat thickness and carcass conformation were evaluated. The average daily gain was higher for supplementation with 1.4% of body weight compared to supplementation with 0.8% of body weight, with no difference between the other levels of supplementation. The age at slaughter was similar between supplementation with 1.1% and 1.4% body weight, being lower for supplementation with 1.1% of body weight compared to supplementation with 0.8% of body weight. Carcass subcutaneous fat thickness was similar between the highest levels of supplementation, being higher with supplementation of 1.1% of body weight compared to supplementation with 0.8% of body weight. The other variables were not influenced by supplements. Feeding with 1.0% of body weight of protein energy supplement is more suitable for finishing young Jersey steers on winter pastures, as it allows for better production efficiency and carcasses with adequate fat finishing.